A New Mechanism of Action in Heart Failure: Angiotensin-Receptor Neprilysin Inhibition. (June 2016) - Richardson, Jonathan; David, Tosin; Grace, Yasmin; Guirguis, Erenie
Objective: To evaluate the efficacy, safety, and clinical significance of sacubitril/valsartan (Entresto) in patients with heart failure with a reduced ejection fraction (HFrEF).Data Sources: An extensive search was conducted on Ovid MEDLINE using keywords and medical subject headings LCZ696, sacubitril/valsartan, angiotensin-receptor neprilysin inhibitor, and Entresto .Study Selection and Data Extraction: The search was conducted to retrieve clinical trials comparing sacubitril/valsartan to current guideline-directed therapy for HF. Articles using the limits of clinical trials "all" (phase I to IV), in English, and published within the past 5 years were reviewed. Supplemental sources included the Entresto package insert via the manufacturer's website. Primary end points included all-cause mortality and time to first hospitalization. Safety end points included incidence and severity of angioedema, cough, hyperkalemia, increased serum creatinine, and hypotension.Data Synthesis: This review critiques both clinical and statistical significance of the "Prospective Comparison of ARNi with ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure" or PARADIGM-HF and other phase II to III clinical trials. Sacubitril/valsartan showed a 20% reduction in cardiovascular death and first hospitalization from HF compared with enalapril. Despite an overall reduction in adverse events, sacubitril/valsartan had increased occurrences of hypotension and nonserious angioedema.Conclusion: Sacubitril/valsartan is a viable option for newly diagnosed New York Heart Association (NYHA) class II to III and is an alternative to patients who are currently being treated with the maximum doses of current gold standard treatment. Clinicians initiating sacubitril/valsartan must monitor patients closely for signs, symptoms, and history of hypotension and angioedema.